Giant Meningioma of the Parieto-Occipital Lobe of the Brain - A Case of Report - Rahman, Md Lutfor; Karmaker, Pranob; Pramanik, Subrota Kumar; Rahim, AM Asif (TAJ: Journal of Teachers Association, 2009)
Most meningiomas are benign and malignant meningiomas are extremely rare . We are reporting a case of giant meningloma of the parieto-occipital lobe of the brain which is quite uncommon. doi: 10.3329/taj.v16i1.3901 TAJ June 2003; Vol.16(1): 30-31